Understanding stakeholder relationships and local context to build a community-based one health surveillance system in Guinea - Maxime Tesch; Abdoulaye Touré; Saa André Tolno; Hélène De Nys; Mathieu Bourgarel; Mamadou Alimou Barry; Mohamed Idriss Doumbouya; Marisa Peyre; Marie-Marie Olive (One Health, 2025)
In 2014, the Ebola virus epidemic that began in Guinea spread to several countries in sub-Saharan Africa, causing the deaths of almost 11,000 people. This crisis, caused in part by increased human contact with wildlife, was exacerbated by the lack of preparedness within the health sector of the affected countries, including inadequate surveillance of disease emergence from wildlife. Given that local communities face the greatest exposure to these issues, this study sought to acquire the contextual knowledge needed to set up community-based zoonotic disease surveillance. Field investigations based on a One Health approach were carried out at two sites in the Guéckédou prefecture in Guinea's forest region. Semi-structured individual interviews and focus group discussions were held with 87 members of the community. These interviews provided new information about zoonotic disease surveillance in Guinea, which we then used to map the health actors and their relationships within the community. We gathered details about the barriers they face and their concerns, such as the fundamental importance of training, a lack of legitimacy, and the differences in means allocated among the human, animal, environmental, health sectors. Some relatively unidentified stakeholders also emerged as possible communication channels. This study shows the importance of talking to the primary users of surveillance to ensure the acceptability and relevance of the surveillance system to the local community. Community members can clearly articulate their priority needs in a given context to ensure potential solutions align with those needs. The epidemiological context in Forest Guinea over the last 10 years makes this region an ideal laboratory for understanding how to tackle emerging infectious diseases in close cooperation with the people most affected.